Cellular Localization and Role of Kinase Activity of PMK1 in Magnaporthe grisea - Bruno, Kenneth S.; Tenjo, Fernando; Li, Lei; Hamer, John E.; Xu, Jin-Rong (Eukaryotic Cell, 2004)
Classifications Services EC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue EC About EC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy EC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1535-9778 Online ISSN: 1535-9786 Copyright © 2014 by the American Society for Microbiology. For an alternate route to EC .asm.org, visit: EC